2023
DOI: 10.1093/jas/skad022
|View full text |Cite
|
Sign up to set email alerts
|

Soluble corn fiber, resistant corn starch, and protected butyrate effects on performance, gastrointestinal volatile fatty acids, and apparent total-tract digestibility of calcium and phosphorus in nursery pigs

Abstract: An experiment was conducted to determine how feeding a calcium (Ca) deficient diet would affect gastrointestinal pH and volatile fatty acids (VFA), Ca digestibility, bone mineral density (BMD), and performance in nursery pigs; and if supplementation of nondigestible oligosaccharides would affect these same parameters. Two hundred and forty weaned pigs (BW = 7.1 kg) were placed into 80 pens with 3 pigs/pen. The 8 dietary treatments consisted of: 1) positive control (PC, 0.83% total Ca), 2) negative control (NC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
1
0
0
Order By: Relevance
“…The present study evaluated the impact of the dietary treatments on VFA concentration in cecal digesta, which showed a consistent increase in acetate, propionate, and butyrate concentration in pigs fed the 40% HA-starch diet. Previous studies have reported similar effects of HA-starch increasing the VFA concentration in the intestinal digesta, especially butyrate concentrations [29][30][31] . Increased VFA production promotes intestinal development and health, especially for butyrate, improving intestinal epithelial cell function and as an energy source for the cells 16,32 .…”
Section: Discussionsupporting
confidence: 56%
“…The present study evaluated the impact of the dietary treatments on VFA concentration in cecal digesta, which showed a consistent increase in acetate, propionate, and butyrate concentration in pigs fed the 40% HA-starch diet. Previous studies have reported similar effects of HA-starch increasing the VFA concentration in the intestinal digesta, especially butyrate concentrations [29][30][31] . Increased VFA production promotes intestinal development and health, especially for butyrate, improving intestinal epithelial cell function and as an energy source for the cells 16,32 .…”
Section: Discussionsupporting
confidence: 56%